P53 Protein Expression in Epithelial Lining of Odontogenic Cysts: An Immunohistochemical Descriptive Case Study - Sohail, Aqib; Amjad, Aneela; Zahid, Nighat; Chatha, Asad Aizaz; Khan, Nauman Rauf; Iqbal, Aamer; Yusuf, Bilal (Journal of Gandhara Medical and Dental Science, 2021)
OBJECTIVES: The current study was conducted to analyze immunohistochemical appearance of P53 protein in odontogenic cysts. METHODOLOGY: Thirty paraffin blocks of confirmed case were prepared to investigate the immunohistochemical appearance of P53 protein. RESULTS: Sixteen out of thirty odontogenic cysts (53.3%) showed P53, four out of ten dentigerous cyst (40%) had P53, twelve out of fifteen odontogenic keratocysts (80%) expressed P53 while none of the five radicular cysts (0%) showed P53 protein. CONCLUSION: Reclassification of OKC as keratocystic odontogenic tumor was supported by the present study and its findings.